Sound velocity and parameter of nonlinearity in the two-component relaxing mixtures - Anna PERELOMOVA (Archives of Acoustics)
General formulae on small-signal sound velocity and parameter of nonlinearity B/A of a two-component relaxing mixture in the two limiting cases of very low and very high periods of sound (when the thermal equilibrium between components has enough time to establish or not) are derived. Sound parameters are expressed in the terms of partial derivatives of individual equations of state. For the two cases: the mixture of van der Waals gases and the suspension consisting of the ideal gas and tiny solid or liquid inclusions, sound velocity and parameter of nonlinearity B/A are evaluated as functions of mass concentration of one of the parts. The first example concerns to the mixtures consisting of oxygen and helium, and the second one to the suspension of air and graphite and the water fog. General conclusions about acoustic features of the two-component mixtures under very high and low frequencies are drawn out.